Perilaku Etis Individu Dalam Pelaporan Keuangan: Peran Pendidikan Berbasis Syariah Dan Komitmen Religiusitas - Nadia Rahma; Rahmani Timorita Yulianti; Hafiez Sofyani (Jurnal Akuntansi dan Keuangan Islam, 2018)
This study aims to examine whether there are differences in ethical behavior on financial reporting by an individual who studied economics and business based on sharia and non-sharia curriculum. In addition, this study also examine whether religiousity commitment influencing ethical behavioron financial reporting. The study employs 2x2 factorial experiments design with research subjects are students from Department of Economics and Islamic Banking and Department of Accountancy. The study reveals that ethical behavior on financial reporting of an individual is affected by sharia education which he/she attended. Detail explanation about the results study can be read in the paper